Effects of cross-cultural training on expatriates’ self-efficacy and adjustment in host country : a study of American, European and Asian managers. - Lee, Edward Kheem Seng. (2008)
Guided by a sound conceptual framework, the objectives of this study are to study the effectiveness of cross-cultural training on perceived self-efficacy of the expatriates and to study the effects of self-efficacy on expatriates' adjustments in Asian context.